2017
DOI: 10.20961/ijpte.v1i2.15078
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perceptions of the Constructivist Instructional Methods in a Teaching and Learning Course

Abstract: Constructivism is defined as building one's own understanding. Constructivist instructional method requires that teacher should not be the one who informs but who facilitates the students learning. The purpose of this study is to obtain the students' perceptions on the implementation of constructivist instructional methods in Teaching and Learning course. A survey research methodology was used with first semester students who were taking teaching and learning course as the subjects of this study. Methods of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
2
0
2
Order By: Relevance
“…It can be concluded that the increase in critical thinking skills in the experimental class is higher than in the control class. Such classroom active setting also suggested to be the rationale behind constructivism that developed during active engagement one another that help students better understand the subject being delivered (Siahaan, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It can be concluded that the increase in critical thinking skills in the experimental class is higher than in the control class. Such classroom active setting also suggested to be the rationale behind constructivism that developed during active engagement one another that help students better understand the subject being delivered (Siahaan, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have indicated that despite there being strong pedagogical and theoretical arguments encouraging classroom interaction, there has been relatively a small body of research done on the efficacy of small group or pair work on second language acquisition (Storch, 2007). Siahaan (2017) argues, while there is a lot of discussion on constructivist teaching approaches, students' perspective on this approach is seldom viewed.…”
Section: Why Constructivism Was the Chosen Pedagogy For The Studymentioning
confidence: 99%
“…Perubahan struktur kognitif dalam pembelajaran matematika merupakan bentuk mengkonstruksi pengetahuan baru berdasarkan kemampuan pemrosesan informasi siswa yang melibatkan beberapa konsep matematika (Navaneedhan & Kamalanabhan, 2017). Para pakar konstruktivis menyarankan untuk memulai dengan pengalaman sehari-hari para siswa, kemudian berusaha untuk merekonstruksi sebuah pengetahuan baru (Siahaan, 2017). Rigorous mathematical thinking atau berpikir matematis Rigor memiliki perbedaan dengan pendekatan konstruktivis populer saat ini, karena lebih menekankan pada memulai sebuah konstruksi pengetahuan dari materi matematika kemudian menerapkan metode, bahasa dan karakteristik operasi dari subjek matematika untuk pengalaman sehari-hari siswa.…”
Section: Pendahuluanunclassified